East of Eden Play Still - Richard Trigg:::Creator::::::::::::
A play still from the Actors Theatre of Louisville for Brown-Forman Classics in the Context Festival. From part 1: 'Pillars of Fire.' Adam Trask (Richard Kuhlman) getting beat up by Sam Hamilton (Jonathan Bolt). Different actors played the same role in this production and the same actor played multiple roles, so there is some cross-over. RESTRICTED USE